PARATE EKSEKUSI PADA HAK TANGGUNGAN DALAM KAJIAN BIAYA SOSIAL (SOCIAL COSTS THEORY) - Dyah Anggraeni (Legal Spirit, 2019)
The research aims to determine the fulfillment of social costs theory when granting parate execution rights to the holders of the mortgage rights, and to determine the form of legal protection for the creditors of the holders of the mortgage rights. The formulation of the problem tested in the discussion, namely: does the granting of parate execution rights to the holders of the mortgage rights meet the theory of social costs ?, and what is the form of legal protection for the creditors of the mortgage holders ?. The research method used is normative research. This research results: 1) The right of execution parate to the holder of the mortgage rights meets the elements of Social Costs theory, this is because the creditor should have been given a right by the debtor to him for default, the debtor is responsible for a default that he did then the creditor was given the right parate execution of a guarantee, and 2) Legal protection of the debtor giving the right of dependents in the perspective of Law No. 8 of 1999 concerning consumer protection and protection of determining the value of guaranteed mortgage rights limit. The juridical reason for the resistance of the debtor granting the mortgageis based on the explanation in Article 6 of the UUHT, where the right to sell on his own strength is not intended ex lege but on the basis of an agreement first.Key words: Execution Parate, Mortgage Rights, Social Costs